Contra Rotating Ducted Propeller Analysis using Computational Fluid Dynamics - Adnan Fadilah, Putra; Furqon Era, Dadang (International Journal of Engineering and Technology, 2018)
Propeller is well known as a mechanical device for propelling a boat or aircraft, consisting of a revolving shaft with two or more broad angled blades attached to it. For now propeller is used in many types of aircraft and boats. This paper is focusing on the propeller, which is applied for small aircraft such as Unmanned Aerial Vehicles (UAV) where the size of the vehicle can be one of the design constraint. Tandem propellers configuration can be an option to cope with the size constraint. This paper studies the performance of tandem propellers in contra-rotating configuration. The study begins with the validation of Computational Fluid Dynamics (CFD) calculation by comparing the results in term of thrust coefficient to the existing performance data. The case study used an UIUC standard 10 inch propeller. The study of contra rotating ducting propeller is performed by analysing the single ducted propeller and followed by the tandem contra rotation ducted propellers set at different axial distances. The results show that the single ducted propeller performs better than open propeller, and there is an optimal distance between propellers in tandem configuration which gives maximal thrust coefficient.Â Â Â Â